Complex training with minimal recovery intervals and their effect on CMJ performance in professional male Rugby Union players - Gowtage, W. J.; Moody, J. A.; Byrne, P. J. (ARC Journal of Research in Sports Medicine, 2020)
In modern day professional rugby union, strength and conditioning specialists have limited time to improve an athlete`s physical qualities. However, Complex Training (CT) can be an efficient alternative training method. Current research suggests an intra-complex rest interval (IRI) of 4 minutes is optimal. However, in a hectic weekly training schedule, this may consume valuable preparation time. This study chose to employ shorter rest periods to determine if performance can be improved with a shorter IRI. Thirteen professional athletes from the Leicester Tigers Development Squad performed 3 repetitions of a front squat at 80% 1RM followed by 7 countermovement jumps either with a 15, 30, 45 or 60 second IRI. A repeated measures analysis of variance found that peak power output significantly improved after 60 seconds rest compared to 15 seconds. Additionally, a significant increase in peak force output was observed in the 4th, 6th and 7th jump following an IRI of 30, 45 and 60 seconds respectively. This study suggests that a 60 second IRI may prove beneficial in a time restricted environment. Furthermore, if an improvement in performance can be elicited in as little as 4 ballistic exposures, this may prove to be an effective minimal dose.